Investigating the impact of brand reputation on brand architecture strategies : a study on a South African automotive company - Waddington, Andrew John (Rhodes University, Faculty of Commerce, Department of Management, 2012)
The brand architecture of an organisation has become increasingly important to global management and marketing professionals, as it deals with structures and designs of brands which are constantly influenced by a changing environment. The market realities and changes brands face continuously impact the reputation of the brand, which is critical to sustain competitive advantage. The primary purpose of the study was to investigate the impact brand reputation has on brand architecture strategies, and an automotive company was chosen as the focus of the research. This research aims to help managers, marketers and brand owners make informative decisions regarding the brand architecture of a company. A quantitative content analysis methodology was used along with a webpage keyword counting application (WebWords). The application was used based on the principles outlined by Corporate Brand and Reputation Analysis (COBRA), which uses a four step progressive filtering process in filtering traditional and consumer generated media. The results from WebWords were then aligned to the brand architecture strategies from the brand relationship spectrum (BRS) to gain insight as to which of the strategies from the BRS were most vulnerable to reputational damage. The study found that the branded house and sub-brand strategies were most vulnerable to reputational damage based on the number reputational hits received. The connection between the master brand and the sub-brands could cause both brands to be affected should any reputational issues arise.
Keywords: Branding (Marketing) -- Case studies; Automobile industry and trade -- South Africa -- Case studies; Toyota JidÅ sha KÅ gyÅ Kabushiki Kaisha -- Case studies; Automobiles -- Marketing -- Case studies; Product management -- Case studies; Branding (Marketing) -- Management -- Case studies; Corporate image -- Management -- Case studies; Brand name products -- South Africa -- Case studies